MEANS OF SUGGESTIBILITY AND THEIR EVOLUTION STAGES IN ARABIC SOCIO-POLITICAL ARTICLES - Dudin, V. (Linguistic and Conceptual Worldviews, 2019)
With the dawn of printed press on the shores of the Arabic speaking world, the methods of impacting an individual’s cognition have been changed for the first time in many centuries. The rise of political and socio-political press in the region overall and in Egypt in particular was likely a by-product of Western intervention in the region, more specifically, Napoleon Bonaparte’s campaign resulting in his temporary control of Egypt. It too was Napoleon who created the first publishing houses in Egypt and it was his political views that were being spread through them. Expanding in detail on multiple sources to delve into the relevant periods, we have worked through numerous newspapers and publishers of socio-political articles in the Middle East and have noticed that Egyptian newspapers have managed to be representative of the Arab speaking printed press in the region. Egyptian editori- als have showcased the forefront of suggestive means with the purpose of leaving an imprint on the reader’s cognition, despite the fact that Egypt was not the first nation with a printed press capable of printing in Arabic. In this study we utilise quotes and examples from a range of socio-political press articles, dated as far back as 1967, as we provide examples backing our hypotheses for the changes in suggestive tactics used by the authors and editorials in their relevant periods. However, our goal in this article was not to focus on the suggestive means themselves in depth, but to rather provide evi- dence pointing to the fact that these suggestive methods have in fact undergone a process of evolution in their own right, changing with time and thus becoming more advanced and author-specific in the process. The possibility to spread a specific subjective position of an author in society without a need for speeches and the accompanying crowds became one of the defining factors to impact and shape the Arab speaking society since the XIX century. The eﬃcacy of suggestive means in printed media has remained in present days with further evolution imminent due to the digitalisation of information, thus making suggestibility a more important aspect of printed press to explore than ever before.